Sistem Pendukung Keputusan Menggunakan Metode Weighted Product untuk Pemilihan Karyawan Terbaik UMKM ZainToppas - Ardi Cahyadi Yudistira; Yunita Sartika Sari (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
Every company needs employees as a force that runs every activity in the corporate organization. In order to achieve the targets that have been compiled by the management, all employees should show maximum performance, therefore to improve the performance of employees so that the targets that have been drafted can be achieved, UMKM ZainToppas will give reward to the best employees that have been chosen, but in the selection of best employees ZainToppas has to implement the right decision support Based on this, it will be built a decision support system by using method weighted product to solve problems that occur in UMKM ZainToppas for the selection of the best employees who are entitled to receive reward in accordance with criteria-criteria that have been determined and more objective. The development of the system using waterfall method and scanning method of weighted product, the output of this system is an alternative that has the highest v vector value, the intended alternative is the employee, then the employee is entitled to receive the reward as the best employee.